Chemical characterization of a novel polysaccharide ASKP-1 from Artemisia sphaerocephala Krasch seed and its macrophage activation via MAPK, PI3k/Akt and NF-κB signaling pathways in RAW264.7 cells. Issue 3 (2nd March 2017) - Ren, Daoyuan; Lin, Dehui; Alim, Aamina; Zheng, Quan; Yang, Xingbin
Abstract : The aim of this study was to investigate the molecular mechanism underlying the immunomodulatory effect of the purified Artemisia sphaerocephala Krasch seed polysaccharide (ASKP-1) in RAW264.7 macrophages. Abstract : The aim of this study was to investigate the molecular mechanism underlying the immunomodulatory effect of the purified Artemisia sphaerocephala Krasch seed polysaccharide (ASKP-1) in RAW264.7 macrophages. Chemical characteristic analysis revealed that ASKP-1 consisted of 14.1% mannose, 56.9% glucose and 19.6% galactose with the average molecular weight of 9.08 × 10 5 Da and the mixed glycan backbone structure containing 1→4)-Glc p (39.8%), 1→6)-Gal p (18.8%), 1→3, 6)-Man p (19.6%), 1→)-Glc p (10.8%), 2→6)-Man p (4.0%) and 2→3, 5)-Ara f (7.0%). In vitro studies showed that ASKP-1 markedly induced the release of cytotoxic molecules (NO and ROS) and secretion of the cytokines (TNF-α, INF-β, and IL-6) and significantly enhanced the phagocytosis of RAW264.7 macrophages. Furthermore, TLR4 was found to be a recognized target of ASKP-1 and its related mitogen-activated protein (MAPK) and phosphoinositide 3-kinase (PI3K)/Akt, including phosphorylated ERK, JNK, p38 and Akt, were rapidly activated by ASKP-1 in RAW264.7 macrophages. Moreover, ASKP-1 was found to cause the nuclear translocation of the nuclear factor NF-κB subunit p65 and the degradation of IκB-α in RAW264.7 macrophages. All these findings suggest that MAPK, PI3K/Akt and NF-κB pathways are involved in ASKP-1-induced macrophage activation, and ASKP-1 is a potential immunomodulating function food.